Influence of home environment on preschool children's cognitive development in Lagelu Local Government Area of Oyo State, Nigeria (2018)
The home environment has been a very important factor in the upbringing of a child. Most children in pre-school age need an environment that is comfortable and stimulating to enhance their learning skills necessary for their development. Without a good home, it is likely that these children will not develop to their maximum capacity, especially in the area of cognitive development. Therefore, this study investigated the influence of home environment on preschool children’s cognitive development in Lagelu Local Government of Oyo State. The study adopted a descriptive survey design. The sample of the study consisted of two hundred and forty-five (245) parents and their children in the nursery sections of public and private schools in Lagelu Local Government Area of Oyo State. Two instruments were used for data collection; Parents’ Assessment Questionnaire (PAQ) and Preschool Children’s Emergent Literacy Assessment (PCELA). The two instruments were validated. A Cronbach’s Alpha reliability coefficient of 0.899 and Guttman Split- half coefficient of 0.572 was obtained, respectively. The data collected were analyzed using frequency counts and percentages; simple regression test was used to answer the research questions. The findings of the study showed that there was a significant joint influence of the four variables used (parents’ education, motivation, style, and adequacy of educational materials) on the cognitive development of children. Parents’ education and motivation were the only home environment factors that significantly influenced the cognitive development of preschool children; while parenting style and adequacy of educational materials did not. Only parents’ education and motivation predicted preschool children’s cognitive development. Based on the findings of the study, relevant conclusions were drawn. It was recommended that educational materials should be made available in the home. Parents should also try as much as possible to show positive attitude towards their children. Parents should always find time to visit their children at school at least on open days so as to know all the developmental aspects of their children.